Pathogenesis of Sepsis - Anggraini, Debie; Hasni, Dita; Amelia, Rinita (Scientific Journal, 2022)
Sepsis is a clinical condition caused by the body's immune response to infection and manifests as SIRS. Systemic inflammatory response syndrome is a state of systemic inflammatory response characterized by two or more of the following conditions. Etiology  Sepsis can be caused by various microorganisms and the most etiology of sepsis is bacterial. Gram-negative bacteria cause sepsis about 60% - 70% in developing countries, but in the United States the causes of infection by Gram-positive bacteria begin to increase. This may be due to the large number of uses of invasive procedures, increased hospital acquired pneumonia (HAP) and antibiotic resistance. The body also has anti-inflammatory mechanisms including increased levels of anti-inflammatory cytokines and glucocorticoid hormones. The hormone inhibits the synthesis of cytokines by monocytes and decreases the ability of neutrophils to attach to the vascular endothelium. The inflammatory process in sepsis is not controlled leading to the occurrence of excessive discharge of inflammatory mediators over a long time and goes beyond the anti-inflammatory mechanisms of the body. This leads to various organ dysfunctions including cardiovascular, liver, pulmonary and renal dysfunctions